Few-body quantum dynamics of high-Z ions studied at the future relativistic high-energy storage ring - Hagmann, Siegbert; Surzhykov, Andrey; Fischer, Daniel (Physica scripta, 2013)
At the FAIR facility for antiprotons and ion research, the high-energy storage ring will provide highly charged heavy ions with Z all the way to Z = 92 for beam energies ranging from 200 A MeV up to energies of approximately 5 A GeV. This opens up a wealth of opportunities for in-ring atomic physics experiments on few-body quantum dynamics ranging from, for example, the correlated dynamics of various e+-e− pair creation processes to quasi-photoionization of inner shells of the highest-Z ions.
Gesehen am 15.10.2021